HUBUNGAN KETERAMPILAN DAN KOMUNIKASI PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN PURWOREJO - Suparni Suparni; Susi Sulandari (Journal of Public Policy and Management Review, 2018)
Public Service Quality especially in the Investment and One Stop Service Agency of Purworejo Regency should be done well, but based on the observations of the researchers, the public service quality in the Investment and One Stop Service Agency of Purworejo Regency is still not good as indicated by the service poll of 46.2%. This is due to online licensing applications that sometimes error and the existence of new regulations Law No. 72 of 2017 concerning Licensing and Non-Licensing Services in the Network. The purpose of the research was to describe and analyze the public service quality, employee skills, employee communication and the relationship between employee skills and communication to public services quality in the Investment and One-Stop Service Agency of Purworejo Regency. The research method used quantitative research methods through survey. Based on the results of data analysis it can be seen that the public services  quality in the Investment and One Stop Service Agency of Purworejo Regency is good with a total average score of 3,09 but there are two indicators that are still low, namely the ease of process indicators in services (2,78) and work tools (2,74). The skills of the employees in the Investment and One Stop Service Agency of Purworejo Regency are already good with a total average score of 3.04 and good employee communication with an average score of 3.05. Employee skills have a strong and significant positive relationship to service quality of 0.704 at a significance number of 0,000 (<0,1), employee communication has a moderate positive relationship of 0,566 and is significant at 0,000 (<0,1), and jointly between skills and communication of employee have a moderate positive relationship of 0,427 and are significant at 0,000 (<0,1). It can be concluded that the public service quality, employee skills, and employee communication in the Investment and One Stop Service Agency of Purworejo Regency is good. Suggestions that researchers can provide for further research related to public service quality please to use different variables.